2009
DOI: 10.1117/1.3143192
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide resonant tuning fork for microsensing applications in high-temperature and high G-shock environments

Abstract: We present the fabrication and testing of a silicon carbide balanced mass double-ended tuning fork that survives harsh environments without compromising the device strain sensitivity and resolution bandwidth. The device features a material stack that survives corrosive environments and enables high-temperature operation. To perform hightemperature testing, a specialized setup was constructed that allows the tuning fork to be characterized using traditional silicon electronics. The tuning fork has been operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Silicon Carbide (SiC) is a silicon-based wide band-gap material, which exhibits strong mechanical properties and is chemically inert. These properties have led to the employment of SiC in a variety of applications due their stability within a multitude of environments: In high-temperature energy conversion devices and in chemically corrosive and high shock environments [ 15 , 16 ]. SiC-based field-effect transistors (FETs) have demonstrated operation for thousands of hours under high-temperature conditions [ 17 ] and SiC NWs have been used in hydrogen sensors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon Carbide (SiC) is a silicon-based wide band-gap material, which exhibits strong mechanical properties and is chemically inert. These properties have led to the employment of SiC in a variety of applications due their stability within a multitude of environments: In high-temperature energy conversion devices and in chemically corrosive and high shock environments [ 15 , 16 ]. SiC-based field-effect transistors (FETs) have demonstrated operation for thousands of hours under high-temperature conditions [ 17 ] and SiC NWs have been used in hydrogen sensors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SiC is more successful in resistance than Si or diamond-like carbon with chemical, wear, mechanical, and oxidation. Myers et al 26 reported that polycrystalline 3C-SiC sensor resonates in air and can operate at 873 K in dry steam. The development of advanced ceramic (e.g., SiC) semiconductors has enabled a new class of sensor and electronics that can operate in hostile conditions and is also believed to contribute to increased fuel efficiency, increased operation lifetime, and reduced emission (in aircraft propulsion, industrial gas turbines, and automotive engines).…”
Section: Introductionmentioning
confidence: 98%
“…Applications for such materials are driven by the extensive sensor, actuator, and MEMS industries. For specific applications, see Rebeiz et al [16], Quandt and Ludwig [17], Grimes et al [18], and Kouzoudis and Grimes [19,20], Azevedo et al [21], Jones et al [22], and Myers et al [23]. In certain instances, these materials are used in conjunction with static magnetic fields to facilitate devices which handle time-varying electrical loads.…”
Section: Introduction and Objectivesmentioning
confidence: 99%